Uremic pleuritis in chronic hemodialysis patients. Issue 1 (20th June 2012) - Rashid‐Farokhi, Farin; Pourdowlat, Guitti; Nikoonia, Mohammad‐Reza; Behzadnia, Neda; Kahkouee, Shahram; Nassiri, Amir‐Ahmad; Masjedi, Mohammad‐Reza
Abstract Chronic hemodialysis (HD) patients are predisposed to several complications associated with pleural effusion. In addition, uremia can directly cause pleuritis. However, there are inadequate data about pathogenesis and natural course of uremic pleuritis. In this study, 76 chronic HD patients with pleural effusion admitted to the Respiratory Center of Masih Daneshvari Hospital, in Tehran, Iran between June 2005 and May 2011 were evaluated to figure out the etiology of their pleural disease. Among these patients, patients with uremic pleuritis were identified and studied. The rate of uremic pleuritis was 23.7%. Other frequent etiologies of pleural effusion were parapneumonic effusion (23.7%), cardiac failure (19.7%), tuberculosis (6.6%), volume overload, malignancy, and unknown. In patients with uremic pleuritis, dyspnea was the most common symptom, followed by cough, weight loss, anorexia, chest pain, and fever. Compared to patients with parapneumonic effusion, patients with uremic effusion had a significantly higher rate of dyspnea and lower rate of cough and fever. Pleural fluid analysis showed that these patients had a significantly lower pleural to serum lactic dehydrogenase ratio, total pleural leukocytes, and polymorphonuclear count compared to patients with parapneumonic effusion. Improvement was achieved in 94.1% of patients with uremic pleuritis by continuation of HD, chest tube insertion or pleural decortication; an outcome better than the previous reports. Despite the association with an exudative effusion, inflammatory pleural reactions in patients with uremic pleuritis may not be as severe as infection‐induced effusions. Owing to the advancement in HD technology and other interventions, outcome of uremic pleuritis may be improved.